Location Quotient Analysis in Identifying Leading Sector in East Lombok Regency 2015-2020 - tati atmayanti; Muhamad Johari; Abdul Hadi Sukmana (UIN Mataram, 2021)
Economic growth is one of the important elements in economic development. The various regional potentials will shape the structure of the economy, so it is very necessary to maximize this potential. Economic sectors that are prioritized in forming GRDP are classified in the leading sector/base sector. This study aims to identify the leading sectors in East Lombok Regency which are used as information and considerations for economic development planning. This type of research is descriptive with a quantitative approach. This study uses secondary data in the form of Gross Regional Domestic Product (GRDP) data from 2015 – 2020 (time series) for East Lombok Regency and West Nusa Tenggara Province. The analytical tool used in this research is Location Quotient Analysis. The results of the Location Quotient Analysis (LQ) show that 9 sectors are identified based on business fields which are the leading sectors, including 1) Processing/Manufacturing Industri; 2) Agriculture, Forestry and Fisheries; 3) Wholesale and Retail Trade, repair of cars and motorcycles; 4) Construction; 5) Government Administration, Defense and Mandatory Social Security; 6) Real Estate; 7) Education Services; 8) Health services and social activities; 9) Procurement of electricity and gas.